Long-term sequelae after viral meningitis and meningoencephalitis are frequent, even in mildly affected patients, a prospective observational study - Schwitter, Janine; Branca, Mattia; Bicvic, Antonela; Abbuehl, Lena S.; Suter-Riniker, Franziska; Leib, Stephen L.; Dietmann, Anelia (Frontiers in Neurology, 2024)
Introduction An increasing number of studies demonstrate that viral meningitis and meningoencephalitis, even those with a mild course of meningitis, can result in residual sequelae. Methods We aimed to investigate the long-term outcome in both viral meningitis and meningoencephalitis/encephalitis patients and impact of long-term sequelae on patients’ social and professional daily lives in a prospective observational study with a follow-up period of 20 months. Results A total of 50 patients (12% encephalitis, 58% meningoencephalitis and 30% meningitis) and 21 control persons participated in the study. The most common cause was the tick-borne encephalitis (TBE) virus. The most important persistent signs and symptoms after 2 years were subjective cognitive impairment (36%), fatigue and/or excessive daytime sleepiness (31%), disturbed nighttime sleep (31%) and headaches (13%), as well as feeling more rapidly exhausted after cognitive effort (53%). Independent of disease severity in the acute phase, almost one third of patients still reported mildly impaired social and/or professional life due to the long-term sequelae, with scores in the health status assessment still significantly lower compared to healthy controls. Discussion Regardless of the severity of the acute illness and despite constant improvement within 2 years, 67% of patients still had persistent signs and symptoms, but these were only relevant to everyday social or professional life in about 30% of these patients.